Using cell-lineage tagging to decipher early differentiation and development in wheat endosperm - Freeman J.; Kurup S.; Huttly A.K.; Shewry P.R. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Wheat grain shape and size affects processing quality and is determined by the timing, location, number and orientation of cell divisions within the grain. We are using a transgenic approach to study cell lineage in wheat endosperm development by inducing expression of nuclear-targeted GFP in young endosperm cells using an Ac/Ds transposon-based system. The system will allow us to mark clonal sectors and follow early endosperm lineage events. The transgenic lines generated will provide a valuable resource for studying development in wheat tissues, including the endosperm, and the knowledge gained will assist in the design of strategies for improving cereal grain yield/quality. Here we report progress in the generation and testing of transgenic wheat lines.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)